Annual Report 2020: Building forward better - Center for International Forestry Research (CIFOR-ICRAF, 2021)
This annual report features stories about expertise, dedication and perseverance. When people responded to the pandemic with calls to ban wild meat, CIFOR-ICRAF experts stepped forward with recent, highly relevant evidence in hand, highlighting the needs of communities who rely on wild game for nutrition. Other scientists forged ahead to deliver compelling research findings on improved tree seed and restoration work in Ethiopia, agroforestry in Southeast Asia, and a new model for sustainable use of woodfuel in refugee camps – among many other topics.